SINERGI UNDANG-UNDANG NOMOR 13 TAHUN 2003 PASAL 156 AYAT 2 DAN HUKUM ISLAM - Siti Nurhayati; E. Mulya Syamsul; Kurnia Rusmiyati (Masoem University, 2019)
Various conflicts between workers and employers always occur. Besides the issue of wage rates, and other related problems. Termination of employment is a latent conflict in the interaction between workers / employers allegedly trying to reduce severance pay, retirement fees, compensation payments, and costs as compensation for layoffs. So that the problem arises in this study about the Synergy of Law No. 13 of 2003 Article 156 Paragraph 2and Islamic Law. With the aim of understanding how the purpose and objectives of the Manpower Act Article 156 Paragraph 2 is reviewed from Islamic Law. The methodology used in this study is a descriptive method with a qualitative approach to the description of severance. And the results of research on the Synergy of Labor Law Article 156 Paragraph 2, is one of the severance pay in Article 156 Paragraph 2 based on the achievement of tenure and the amount of salary / wages. The lowest value for tenure less than one (1) year is one (1) wage month, while the lowest value for tenure more than eight (8) years is nine (9) wage months. And the provision of severance pay is made when the employee stops working. The view of Islamic law on the obligation to pay severance pay as compensation for layoffs is a mandatory law, as Islam requires the strengthening of contractual agreements for work to ensure the rights and upholding of justice among all people, and Islam also considers that the contract is carried out in accordance with the rules that have been stipulated and agreed.